Language and Style of Communication of Samin Community in Kudus, Central Java - Mahfudlah Fajrie; M. Zanuar Rohman Alwi; Yuyun Wahyu Izzati Surya (Universitas Airlangga, 2022)
This study aims to find out the style of language and communication used by the Samin Karangrowo community with their fellows and others outside the community. The Samin community, located in Karangrowo Village, Undaan District, Kudus Regency, is assumed to have unique style of language and communication due to their different attitude, behavior, and social conditions compared to others in Kudus Regency. Qualitative method with ethnographic approach is used in this study. This study then reveals that Samin Javanese language is mostly used in the Samin Karangrowo community. This study also finds out that Jawa ngoko and krama inggil are mostly used by the Samin people to communicate with others outside their community. Besides, the results of this study indicate that equalitarian style is frequently used by the Samin Karangrowo community as their communication style with their fellows since it is considered to be very effective for them in making decisions wisely as well as in solving their problems. However, in communicating with others outside the community, they mostly use controlling style as their communication style to protect the customs and culture of the Samin community from outside cultures. Finally, it can be concluded that the Samin community is strongly upholding the teachings of Sedulur Sikep in their communication strategy.